Evaluation of the Implementation of Occupational Safety and Health in the Preservation of the Aimas-Klamono Road, Sorong Regency - Gebion Lysje Pagoray (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The Preservation of the Sorong City Boundary Road is located on the Sorong Regency road section. This area is densely populated so it is in dire need of improving road services to support all land traffic activities. The research location for the evaluation of the application of occupational safety and health on the preservation of the Aimas – Klamono – Sorong Regency road is located on the Sorong Regency – South Sorong Regency road section. To reach the research location, the distance taken is 18 km from Sorong City. This study aims to determine the implementation of K3 on the construction project of the Aimas – Klamono Road Section, Sorong Regency. Primary data was obtained by observing, conducting interviews, and filling out checklists. The results of the implementation of SMK3 are Workplace Safety in the Project with a weight of 81.83%, Work Equipment and Clothing 91.96%, Protection of the Public 71.06%, Management Commitment to Occupational Safety and Health (K3) 54.44%, Occupational Health with a weight of 76.67%